Tiredness after work associates with less leisure-time physical activity - Sjöros, Tanja (Springer Nature, 2025)
Physical activities and sedentary behaviors take place in different contexts. This study aimed to determine if the context, total score, and leisure-time MET-index assessed by the Baecke questionnaire associate with each other or with sedentary behavior and physical activity outcomes from a 4-week accelerometer measurement in physically inactive adults with overweight. The item "After working I am tired" correlated negatively with items related to leisure-time physical activity and sports participation. The total Baecke Score showed weak but significant correlations with accelerometer-measured sedentary behavior, physical activity, daily steps, and mean activity intensity of the day (r = - 0.33, 0.41, 0.35, and 0.41, respectively). The associations strengthened when the Sport Index was omitted from the Score. The leisure-time MET-Index did not correlate with accelerometer-measured sedentary behavior or physical activity. Tiredness after working associated with less self-reported physical activity during leisure time. This suggests that better recovery from work-related stress could increase leisure-time physical activity, or increasing leisure-time physical activity could reduce tiredness after working. Moreover, among self-reportedly inactive adults with overweight, focusing the questionnaire on work and non-sport leisure time instead of total time might give more accurate estimates of sedentary behavior and physical activity when compared to accelerometry.The study is registered at ClinicalTrials.gov (NCT03101228, 05/04/2017).